2007
DOI: 10.1097/01.ogx.0000271108.07912.1e
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Vertical Hepatitis B Transmission by Hepatitis B Immunoglobulin in the Third Trimester of Pregnancy

Abstract: Passive-active immunoprophylaxis with hepatitis B immunoglobulin (HBIG) and hepatitis B vaccine provides a high level of protection against vertical transmission of hepatitis B virus (HBV). Nevertheless, 1 in 10 children of HBV carriers have chronic hepatitis B early in their lives despite immunoprophylaxis because they were infected in utero. This study of 469 pregnant women testing positive for hepatitis B surface antigen (HbsAg) was conducted to learn whether giving HBIG to HBV carriers in the third trimest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 0 publications
0
32
0
7
Order By: Relevance
“…Pek çok çalışmada immünopro-filaksi başarısızlığı için en önemli risk faktörleri, annenin HBeAg pozitifliği ve yüksek HBV DNA düzeyi olarak bulunmuştur (4,12,13,15,(17)(18)(19)21,26,31) . Wang ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Pek çok çalışmada immünopro-filaksi başarısızlığı için en önemli risk faktörleri, annenin HBeAg pozitifliği ve yüksek HBV DNA düzeyi olarak bulunmuştur (4,12,13,15,(17)(18)(19)21,26,31) . Wang ve ark.…”
Section: Discussionunclassified
“…Gebelik döneminde HBV DNA seviyeleri yüksek gebelerde nükleozid analogları (NA) kullanılmasının viral yükü azaltarak etkili olabileceği ve doğumda aşı ve HBIG uygulamasına ek olarak gebeliğin son trimesterinde lamivudin ve telbivudin tedavisinin güven-li olduğu ve intrauterin geçişi azalttığı saptanmıştır (12,13,22,31,34) . Perinatal bulaşın en önemli bulaş yollarından biri olduğu ülkemizde HBsAg taşı-yıcı gebelerin ve çocuklarının takipleriyle ilgili halen genel bir görüş ve yeterli bir çalışma olmadığından çeşitli aksaklıklar yaşanmaktadır.…”
Section: Introductionunclassified
“…The differences with other studies may be due to sample size, methods used and prevalence of HBV in that region. The world was divided into three separate groups regarding the prevalence of HBV [10] and our study showed HBsAg + was 5% which is in the moderate prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent vertical transmission, passive and active immunization of the neonates immediately after birth with HBIG and anti-HBV vaccine is used, especially in HBeAg + mothers with high viral load [85,86]. In these high viral load pregnant women (HBV-DNA >8log 10 copies/ml), HBIG has been administered monthly in the third trimester of the pregnancy, yielding better results [87,88]. Thus, even intrauterine/ transplacental transmission of HBV can be prevented, which is reported to reach 8% of the cases in women with high viral load and/or preterm labor [89].…”
Section: Pregnant Women With Hepatitis Bmentioning
confidence: 99%